Synthesis and reactivity of a new oxidation-labile heterobimetallic Mn6Zn2 carbamate cluster and precursor to nanosized magnetic oxide particles - Domide, Dan; Hübner, Olaf; Behrens, Silke; Walter, Olaf; Wadepohl, Hubert; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
The synthesis and characterization of the new octanuclear mixed carbamate complex [Zn2Mn6(μ4-O)2(O2CN(iPr)2)12] is reported. This complex is readily oxidized by O2 to give [Zn2Mn6(μ4-O)2(μ3-O)(O2CN(iPr)2)12] featuring a central O atom statistically distributed over two sites within the void of the inner Mn6 cage of the carbamate complex. In relation to the situation before oxidation, the metal cage is expanded by a change of the carbamate bonding mode. The two carbamate complexes were used as precursors to magnetic oxide nanoparticles under mild conditions (210-270 °C depending on the heating rate). A mixture of crystalline ZnMn2O4 and MnO nanoparticles resulted. The experimental data are complemented by some quantum chemical (DF) calculations.
Im Titel ist "6" bei Mn und "2" bei Zn tiefgestellt
Gesehen am 20.06.2022